Effectiveness of Aspergillus sp. extract in denture adhesive on surface roughness of acrylic resin on Candida albicans biofilm formation - Fadriyanti, Okmes; Nasution, Ismet Danial; Siswomihardjo, Widowati; Handayani, Dian (Majalah Kedokteran Gigi Indonesia, 2023)
The denture adhesive increases retention on the denture base and affects oral microorganisms. Adding antifungals to denture adhesives can inhibit the Candida albicans biofilms formation and prevent denture stomatitis. The combination of denture adhesives and herbal medicines is an alternative to antifungals, which have few side effects because it is a plant. Moreover, one of them is the endophytic Aspergillus sp. extract containing chemical compounds that can inhibit the Candida albicans biofilms formation. This study aims to analyze the effectiveness of the endophytic Aspergillus sp. extract in denture adhesive materials for Candida albicans biofilm formation on acrylic resin surfaces. The research method is to extract the Aspergillus sp. extract antibiofilm test. Denture adhesive formulation was adjusted to the standard, and added Aspergillus sp. with concentrations of 3.125%, 6.25%, 12%, and 25%. The research sample used hot polymerized acrylic resin. The control group used X denture adhesive and added nystatin, each group suspended by Candida albicans for 24, 48, and 72 hours. Examination of biofilm formation activity on the surface of acrylic resin used SEM. The analysis used Two Way Anova. Aspergillus sp. extract in denture adhesive effectively prevents Candida albicans biofilm formation within 24 hour incubation time. In conclusion, extract of the endophytic Aspergillus sp. in denture adhesive can inhibit the formation of Candida albicans biofilm on the surface roughness of acrylic resin.